Pharmacological Treatment of Obesity in Patients with Polycystic Ovary Syndrome - Kahal, Hassan (Hindawi Publishing Corporation, 2011)
Polycystic ovary syndrome (PCOS) is a common disorder affecting women of reproductive age and it is associated with increased cardiovascular risk. Obesity plays an important role in the pathogenesis of PCOS, and the majority of patients with PCOS are obese. Over the last 20 years, the prevalence of obesity has dramatically increased, with probable associated increase in PCOS. Weight reduction plays an integral part in the management of women with PCOS. In this paper, current available weight reduction therapies in the management of PCOS are discussed.